AB1040 The Value of Ultrasonography in the Evaluation of Hand Gouty Arthritis – A Comparison with Conventional Radiography. (9th June 2015) - Musetescu, A.E.; Criveanu, C.; Vreju, F.; Florea, M.; Bumbea, A.; Rosu, A.; Ciurea, P.
Abstract : Background: Gout represents a frequent inflammatory rheumatic disease affecting peripheral joints with an increasing prevalence in our country. Musculoskeletal ultrasound is an emerging tool of increasing interest able to detect both structural and inflammatory lesions and facilitate disease diagnosis and monitoring. Objectives: To demonstrate, assess and quantify the pathological findings associated with chronic gout in the second metacarpophalangeal (MCP) joint through musculoskeletal ultrasound in comparison with conventional radiography. Methods: We evaluated 24 patients previously diagnosed with chronic gout and at least one episode of hand arthritis. Ultrasound evaluation was performed by a trained rheumatologist unaware of the clinical data using a Prosound α7 equipment with a multifrequency linear probe and using the standardized scanning technique. The following pathological findings were recorded on ultrasound: cortical erosions defined as breaks in the cortical contour of metacarpal head or proximal phalanx, seen in two perpendicular planes, tophaceous deposits defined as hyperechoic crystalline concrements and calcified tophi defined as hyperechoic aggregates with posterior acustic shadow. Conventional radiographs of anteroposterior and lateral view of the hand were assessed by a trained rheumatologist in the absence of the clinical and ultrasonographic data considering as pathological findings suggestive for gout. Both methods evaluated in a qualitative manner the abnormal findings (presence or absence) Results: We assessed 24 patients (21 males, 3 females) with a total number of 48 MCP joints evaluated. Compared to conventional radiography musculoskeletal ultrasound detected significantly more erosions (p<0.001). Erosions were detected in 23/48 joints (47.9%) compared to only 5/48 joints (10.4%) through conventional radiography. In addition to structural lesions ultrasound was able to detect inflammatory changes associated with gout. Intra-articular tophaceous deposits were detected in 39/48 joints (81.2%) using ultrasound while conventional radiography could not detect un-calcified tophaceous material. Intra-articular calcification of the tophaceous material was seen in 3/48 joints (6.2%) using ultrasound and in 2/48 joints (4.16%) using conventional radiography. Conclusions: Musculoskeletal ultrasound is an extremely valuable tool in the evaluation of gouty arthritis of the hand identifying a significantly higher number of erosions compared to radiographic evaluation as well as in visualizing the intra-articular tophaceous deposits. While uncalcified tophaceous deposits are missed by the conventional radiologic evaluation, calcified tophi are seen by both imaging methods. Disclosure of Interest: None declared